The relationship between service experience equity and guests’ behavioral intention at eco-resorts: A study using PLS-SEM - Hashim, Nurhazirah; Haque, A. K. M. Ahasanul (Association of Malaysian Environment-Behaviour Researchers (AMER); ABRAmalaysia, 2017)
Guest experience studies and the consequences towards behavioral intention have gained attention by recent scholars since the experience of guest play a big role in the success of an organization especially in resort setting. This consequently leads to resort businesses focusing on their guests‘ needs, wishes and desires to make their service hospitable, thus creating a true experience that leads to loyal resorts‘ guests. It is noted that Malaysia has a remarkable significance of the natural attractions to the tourists. Hence, the government highly increased initiatives to continue developing sustainable ecotourism and balancing the environment and development of resorts. This action makes the resorts owners creating favorable infrastructures in order to provide a memorable experience through the design of their resorts. Subsequently, the importance of the service experience equity is strictly undeniable. However, this issue is minimal considered by scholars and practitioners especially in Malaysia. Therefore, this study attempts to investigate the relationship between service experience equity and behavioral intention at eco-resorts. This study also aims to discover the new experience and phenomenon of ecotourism particularly in eco-resort setting in Malaysia. There is also an urgency to explain the new model pertaining to the antecedents of behavior intention among the tourists and guests staying at Malaysia‘s eco-resorts. This study is quantitative in nature and the selection of respondents is based on purposive sampling. With regards to the aim of this study, the result of the hypotheses is tested using partial least square of structural equation modeling (PLS-SEM) and several conclusions were achieved. Noticeably, the exogenous constructs (service experience equity) of this study showed significant influence on the endogenous variable (behavior intention) both individually and collectively. The finding of this study is recommended to enhance the guest experience equity in staying at eco-resorts and foster the remarkable image of eco-resorts among tourist to visit Malaysia.